X-RA: uma análise de intervalos para programas em redes - Luiz Felipe Zafra Saggioro (2015)
This work presents a strategy to improve the integer range analysis on networked programs by taking advantage of a key characteristic. The integer range analysis is one strategy to detect integer overflow occurrences in programs. Even though this analysis can be applied to networked programs as-is, the proposed approach aims at taking advantage of the messages that programs send to each other to improve the integer range analysis. To validate this claim, we have implemented our solution on top of LLVM compiler. We have applied this analysis on some applications and the result shows that our proposal has better results than the conventional approach in terms of defined variables.